Using cultural historical activity theory to understand how post-graduate residents perform discharge planning at a medical center in Taiwan - Fang- Yih Liaw; Yaw-Wen Chang; Po-Fang Tsai (BMC Medical Education, 2024)
Abstract Background Despite the importance of discharge planning in physicians’ education, currently in most countries, no identical training is provided. Difficulties in promoting physician discharge planning education in Taiwan are still noted. This study aims to find the physicians’ role of discharge planning training in educating post graduate year residents (PGY) in Taiwan. Materials and methods We took advantage of government and hospital policies that promote the discharge planning program to teach and implement it, beginning with PGY residents by incorporating it into their training program. We recruited 30 PGY residents who were attending their three-month general internal medicine training from 2018 to 2019. They were interviewed at the end of the program using cultural-historical activity theory (CHAT). Qualitative research methods were used to further understand how discharge planning and care was implemented. Results Trainees initially believed that they did not have any role in discharge planning. Using the cycle of expansive learning, we found that the role of physicians in discharge planning was unclear. There were still some inconsistencies in the teaching and implementation of the discharge planning program for PGY residents that needed to be resolved, but this study also let participants learn through practice to improve their identification of discharge planning. Conclusions This study analyzed the impact of a discharge planning program for PGY physicians in Taiwan. It showed that the program affected physicians’ practice and medical education, although some contradictions remain.